Do merger-related operating synergies exist? - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2011)
Executives frequently forecast large operating efficiency gains from mergers. Using these projections, we study the impact of operating synergies on merger performance. Investors' reaction to mergers varies directly with the availability of these forecasts and the gains they imply, and post-merger operating performance increases with the predictable component of forecasted synergies based on deal characteristics. The realized improvements, however, do not depend on the availability of forecasts or the surprise they convey, and post-merger stock returns reconcile discrepancies between investors' ex ante beliefs and mergers' ex post performance related to management forecasts. Overall, the evidence supports the neoclassical view that expectations and realizations of synergistic gains are important determinants of merger activity and performance.